Validation of the fear of COVID-19 scale in a central Balkan country - Serbia - Zivkovic Zaric, Radica; Zaric, Milan; Canovic, Petar; Jankovic, Slobodan; Stojadinovic, Milorad; Zornic, Nenad; Nesic, Jelena; Spasic, Marko; Jovanovic, Dalibor; Jug, Martina; Jakovljevic, Stefan; Pejcic, Ana (Frontiers in Public Health, 2022)
Validation of the fear of introduction High levels of fear of COVID-19 may be associated with increased levels of stress, anxiety, and depression, as well as decreased resilience and life expectancy. Objective This study aimed to translate and confirm the Serbian version of the Fear of COVID-19 scale as well as to investigate its psychometric properties. Methods The translation and intercultural adaptation of the Fear of COVID-19 scale was performed by the leading standard of the International Society for Pharmacoeconomics and Outcome Research. When the distribution was normal, the Kolmogorov-Smirnov test was used. The reliability of the Serbian version of FCV-19S was tested by measuring the internal consistency through the value of Cronbach's alpha. Results The original version of the Fear of COVID-19 scale was tested on a sample of 256 subjects with a mean age of 25.38 ± 12.47. The Cronbach's alpha value was 0.864. We divided the scale by the split-half method (Spearman-Brown), and the value of the coefficient for the questionnaire as a whole was 0.882. Divergent criterion validity was tested through the non-parametric correlation between the scores of the Fear of COVID-19 scale and the Fear of Hospitalization scale. A score of the Fear of COVID-19 scale was calculated as the sum of each question for each of the respondents. Convergent criterion validity was tested through the non-parametric correlation between the scores of the Fear of COVID-19 scale and the Emotional Regulation Questionnaire. Conclusion The validated version of the scale in Serbia complements versions available in other cultures and other languages and facilitates global studies related to mental health during the COVID-19 pandemic.